The Influence of Covid-19 Cases and Sentiments on Indonesia Stock Market Trends - Azzahra, Muthiara Adlin; Syakurah, Rizma Adlia; Puspita, Wulan Dri (Ekonomi Bisnis, 2022)
This study determined the COVID-19 cases and sentiments effect on the stock price index of selected sectors in Indonesia. The study applied time-series data from the period 2 March-27 October 2020 by collecting data on COVID-19 cases, Indonesia Stock Index (IDX), 10 selected sectors (Jasica) and Google Trends (GT). The researchers used the search terms related to COVID-19 sentiments. The researchers used descriptive analysis for IDX and GT data and applied quantitative analysis with time lag correlation to analyze data based on COVID-19 cases and GT data on the IDX & 10 selected sectors. The researchers used the Manufacture and Mining sectors with the high-or-low negative correlation groups; IDX, Finance, and Miscellaneous Industry with the moderate-or-low negative correlation groups; Trade with the high-or-moderate-or-negligible negative correlation; Agriculture with the high-or-low-or-negligible negative correlation; Consumer Industry with high-or-negligible negative correlation group; Basic Industry and Infrastructure sectors with the moderate-or-negligible negative correlation groups; and Property sector with negligible correlation group. The correlation results showed different effects regarding the sentiments of COVID-19 in each sector.